The Clinical Relevance of Serum Interleukin-21 in Grading Acne Vulgaris - Ayu Kusuma Dewi; Muhammad Eko Irawanto; Arie Kusumawardani; Nugrohoaji Dharmawan; Nurrachmat Mulianto (Journal of Social Research, 2025)
Acne vulgaris (AV) is an inflammatory skin disorder with multifactorial pathogenesis involving genetics, hormones, and immune dysregulation. Interleukin-21 (IL-21), a pleiotropic cytokine mainly secreted by T follicular helper and Th17 cells, has been implicated in various inflammatory skin diseases. However, its role in AV remains unclear. This cross-sectional study included 46 patients with AV, classified into mild (n=19), moderate (n=16), and severe (n=11) groups. Serum IL-21 levels were measured using an enzyme-linked immunosorbent assay (ELISA). Baseline characteristics were compared across groups, and interobserver reliability of AV severity grading was evaluated using Cohen’s kappa test. One-way ANOVA was applied to assess differences in IL-21 levels among severity groups, with a significance level set at p<0.05. The mean serum IL-21 level was highest in the severe AV group (303.53 pg/mL), followed by the moderate (223.7 pg/mL) and mild (213.2 pg/mL) groups. Although there was a trend toward increasing IL-21 levels with higher AV severity, statistical analysis revealed no significant difference among the three groups (p=0.130). Serum IL-21 levels were elevated in AV patients compared with previously reported healthy controls but did not differ significantly across severity levels. These findings suggest that IL-21 may play a role in the pathophysiology of AV, though it is not a reliable marker of clinical severity. Further case-control and tissue-based studies are needed to clarify its role.